Palaeoproterozoic U-PbSHRIMP zircon age from basement rocks in Bangladesh: A possible remnant of the Columbia supercontinent - Hossain, Ismail; Tsunogae, Toshiaki; Rajesh, Hariharan M.; Chen, Bin; Arakawa, Yoji (Comptes Rendus Geoscience, 2007)
We present new U-Pb SHRIMP zircon geochronological data for basement rocks in Bangladesh, and discuss the relationship with the formation of the Columbia supercontinent. Euhedral zircons from a diorite sample yield a concordia age of 1730 +/- 11 Ma, which is interpreted as the crystallization age. The Palaeoproterozoic age of the examined basement rock and the common occurrences of similar similar to 1.7-Ga geologic units in the Central Indian Tectonic Zone and Meghalaya-Shillong Plateau in Indian Shield suggest their apparent continuation. This, together with the occurrence of similar similar to 1.7-Ga geologic units in the Albany-Fraser belt in Australia and East Antarctica, are used to suggest that the basement rocks in Bangladesh formed towards the final stages of the assembly of the Columbia supercontinent. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000251997800004&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 Geosciences, Multidisciplinary SCI(E) 10 ARTICLE 16 979-986 339